KALIBRASI NILAI KEKASARAN MANNING PADA SALURAN TERBUKA KOMPOSIT (KERIKIL-KACA) TERHADAP VARIASI KEDALAMAN ALIRAN (KAJIAN LABORATORIUM) - M. Kamil; M. Baitulah Al Amin; Reini S. Ilmiaty (INFO-TEKNIK, 2014)
Roughness channel factor, widely known as Manning’s value, is an important parameter in open channel flow analysis. For channels with different material composition or composite channels, determination of Manning’s values becomes difficult enough to be done. This study aimed to investigate how flow depth variations affect  Manning’s values of composite channel. The research was done by examining and calibrating the Manning’s values for glass sided flume with gravels on the bed of channel, namely gravel-glass channel . The observation of water surface profiles and flow velocities used  five variation of flow depths in the upstream with a weir in the downstream of channel (0.4 m , 0.35 m , 0.3 m , 0.25 m , 0.2 m) and also without a weir. The channel had a rectangular cross section with a width of 0.3 m and  bed slope 0.0001. The calculation of water surface profiles for composite channel used direct step method. The results pointed out that the Manning’s value of  gravel-glass channel was grealyt influenced by water surface profiles along the channel. For Mild 1 (M1) profile, Manning’s value became smaller as decreasing of flow depths, while for M2 profile, Manning’s value became greater as decreasing of flow depths. Key words: Manning’s coefficient equivalent, composite channel, direct step method, water surface profie simulation